PENGARUH RESILIENSI DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PERAWAT DI RUMAH SAKIT KOTA TANGERANG YANG DIMEDIASI OLEH KEPUASAN KERJA - Bilqis Pramudiya W (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
This study examines the influence of resilience and transformational leadership style on performance mediated by job satisfaction. This study examined 230 inpatient nurses in Tangerang City as a sample. The sample was selected using a non-probability sampling technique through a purposive sampling technique with the criteria of 18–40 years of age and a minimum work period of 6 months. The instruments used included the Individual Work Performance Questionnaire (Koopmans et al., 2013) to measure performance, the Connor-Davidson Resilience Scale (Connor & Davidson, 2003) to measure resilience, the Multifactor Leadership Questionnaire (Bass et al., 2003) to measure transformational leadership style, and the Job Descriptive Index (Smith et al., 1969) to measure job satisfaction. Data analysis was performed using path analysis. These findings confirm that improving nurse performance can be achieved through strengthening individual resilience and implementing an effective transformational leadership style, with job satisfaction as a key factor through this relationship. This research is expected to provide theoretical contributions to the development of industrial and organizational psychology studies, as well as practical implications for hospital management in designing interventions to improve nurse performance.